Forest stand factors determine the rainfall pattern of crown allocation of Picea schrenkiana in the northern slope of Mount Bogda, Tianshan Range, China - Zhao, Shanchao; Zheng, Xin-Jun; Yin, Lihe; Wang, Yugang (Frontiers in Plant Science, 2023)
The middle elevation forest of the Tianshan Mountains, dominated by the conifer tree Picea schrenkiana, is an important part of the mountain ecosystem of arid Northwestern China, which plays a pivotal role in carbon sequestration and water conservation. As the first interface of water transfer in a forest ecosystem, tree crown allocates precipitation regulating soil water supply and sustaining vegetation growth below the crown. In this study, four 20-m × 20-m sampling quadrats were randomly installed at each of three elevation sites (2,200 m, 1,800 m, and 1,450 m) on the northern slope of Mount Bogda, the main peak of the Eastern Tianshan Range. The effects of forest stand factors and incoming rainfall on forest crown allocation of precipitation were investigated, and the trade-off between water and carbon was also discussed. The results revealed that (1) the interception, throughfall, and stemflow ratio had values of 44.3%–50.0%, 49.6%–55.4%, and<0.5%, respectively; (2) there was a complementary relationship between stemflow ability and threshold rainfall when stemflow emerged, and the crown interception rainfall had a saturation value; and (3) the allocation of crown-intercepted rainfall was controlled by trunk diameter at breast height, crown height-to-width ratio, and leaf area index, which was why differences arose in the allocation of crown precipitation at differing elevations. With greater arbor biological carbon density, the crown interception ratio initially increased rapidly but then remained stable, indicating that once a natural forest stand is mature, its biomass carbon sequestration would not change further allocation of crown precipitation.